The socio-economic implications of conversion from commercial agriculture to private game farming: The case study of Cradock, a small town in the iNxuba Yethemba Municipality, Eastern Cape Province, South Africa - Zungu, Vincent Mduduzi (Department of Sociology, 2018)
This thesis sets out to investigate the socio-economic consequences or implications on the township people in Cradock (a town located in iNxuba Yethemba Municipality, Eastern Cape Province of South Africa) of the recent conversions from commercial agriculture to private game farming (PGF). The study draws primarily on research conducted in the town, the history of which is rooted in the development and expansion of commercial agriculture that took place in the early 1800s. It is specifically concerned with the effects of the conversion of agricultural land to game farming on the socio-economic conditions of black African and coloured township people, who have directly or indirectly depended on commercial agricultural production for many decades past. These people have, over the last 200 years, benefited from commercial agriculture through employment, material resource supplies and off-farm activities. These three kinds of socio-economic mechanisms played a crucial role in sustaining the socio-economic conditions of the Eastern Cape's semi-arid towns, such as Cradock, in particular, of those citizens who reside in the townships. By using the de-agrarianisation thesis as a theoretical framework, the study argues that the agrarian change in the form of conversion towards private game farming industry is a form of the de-agrarianisation process, not the proliferation of off-farm activities or off-farm employment, as postulated by Bryceson and Jamal (1997). The study addresses the current debate about the implications of agrarian change emerging in the semi-arid area of the Eastern Cape and in South Africa. At an empirical level, the study seeks to test the proponents of private game farming who argue that game farming in formerly agrarian areas generates national revenue and provides multiple socio-economic benefits to the poor and marginalised people. Part of the context in which the discussion in this study takes place is the role that the development of agricultural land aims to play in improving the socio-economic status or The study uses the economic history of agrarian economy in the Karoo and its production in relation to black Africans as an approach to analyse the effects of conversion. It critically examines the dynamics related to the contribution of private game farming in Cradock, an area historically known as an agricultural stronghold. The study thus argues that the recent introduction of private game farming in the formerly agrarian areas has established an elitist economy that is virtually inaccessible to the people of the area, especially the poor and previously marginalised people residing in the townships of Cradock. The study uses qualitative research design and various qualitative data collection methods such as interviews, household interviews, focus group interviews and qualitative observation, to unpack the socio-economic implications of conversions from the perspective of the township residents. The findings of the study indicate that while the introduction of private game farming industry in Cradock has generated employment for some township people, the industry has negatively affected the socio-economic livelihoods of these people. Although they receive a wage higher than what they received in the former commercial agriculture, the study reveals that their livelihoods are severely and negatively affected by the conversion, as they now have restrained access to the material resource supplies they used to access when the land was used for commercial agriculture. This, in turn, has resulted into the decline of off-farm activities such as butcheries, informal trades, and the trade in and selling of agricultural implements that were an integral part of the former agrarian economy of the town.